Adrenal Neuroblastoma in an Adult: Effect of Radiotherapy on Local Progression after Surgical Removal. (27th July 2016) - Kurokawa, Satoshi; Mizuno, Kentaro; Nakane, Akihiro; Moritoki, Yoshinobu; Nishio, Hidenori; Kamisawa, Hideyuki; Kubota, Yasue; Okada, Atsushi; Kawai, Noriyasu; Hayashi, Yutaro; Yasui, Takahiro
Abstract : Here, we report the case of a 62-year-old man with neuroblastoma, which is extremely rare in adults. His tumor was resected, but it recurred four months later. Radiotherapy reduced tumor size, and the patient remained in good health three years after surgical tumor removal. The residual tumor and the treatments administered to this patient were evaluated. We have also reviewed the literature.